1976
DOI: 10.1111/j.1600-0447.1976.tb00059.x
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Tolerance and Serum Lipids Inman After Long‐term Lithium Administration

Abstract: Intravenous glucose tolerance and serum lactate concentration during the tolerance test were determined in the same 12 patients after 6 months of placebo and after 6 months of lithium treatment. At the end of these periods values of glucose, lactate, serum free fatty acids, and serum triglycerides were measured in fasting patients. Long-term lithium treatment had no influence on these parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
2

Year Published

1978
1978
2007
2007

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 16 publications
1
7
0
2
Order By: Relevance
“…Effects of lithium on the utilization of carbohydrates have been studied mainly by the glucose tolerance test. An increase in glucose tolerance in subjects given lithium was found by Vendsborg and Rafaelsen (1973), van der Velde and Gordon (1969), and Piirgyi (1972), a decrease was demonstrated by Shopsin et al (1972) while no reliable effect of lithium on glucose tolerance was noted by Vendsborg and Prytz (1976). Un fortunately, differences in the experimental conditions used in these studies preclude direct comparisons between them.…”
Section: Introductionmentioning
confidence: 79%
“…Effects of lithium on the utilization of carbohydrates have been studied mainly by the glucose tolerance test. An increase in glucose tolerance in subjects given lithium was found by Vendsborg and Rafaelsen (1973), van der Velde and Gordon (1969), and Piirgyi (1972), a decrease was demonstrated by Shopsin et al (1972) while no reliable effect of lithium on glucose tolerance was noted by Vendsborg and Prytz (1976). Un fortunately, differences in the experimental conditions used in these studies preclude direct comparisons between them.…”
Section: Introductionmentioning
confidence: 79%
“…Some studies found an increase in glucose tolerance after 1 day [ Vendsborg and Rafaelson, 1973], but no effect after 6 months [Vendsborg and Prytz, 1976]. On the other hand, Shopsin et al [1972] found a decrease in glucose tolerance after 2 weeks of lithium therapy.…”
Section: Lithium Drug Interactionsmentioning
confidence: 98%
“…Auch die Wirksamkeit von Lamotrigin ließ sich nicht in einen Zusammenhang mit Gewichtsveränderungen bringen [83]. Ein höheres Ausgangsgewicht und höherer BMI prädisponierte zur Gewichtszunahme unter Lithium−Behandlung [87,160]. Frauen waren von Gewichtszunahme unter Lithium stärker betroffen als Männer [160].…”
Section: Stimmungsstabilisiererunclassified
“…Ein höheres Ausgangsgewicht und höherer BMI prädisponierte zur Gewichtszunahme unter Lithium−Behandlung [87,160]. Frauen waren von Gewichtszunahme unter Lithium stärker betroffen als Männer [160]. Die zugrundeliegende psychiatrische Patholo− gie wurde von Vestergaard und Baptista als weiterer Faktor un− terschiedlich ausgeprägter Gewichtszunahme während der Li− thiumeinnahme gewertet [161,162].…”
Section: Stimmungsstabilisiererunclassified